DESIGN OF INFORMATION AND COMMUNICATION SUPPORT OF SCIENTIFIC RESEARCH ON THE EPRINTS BASIS - Svitlana M. Ivanova (Інформаційні технології і засоби навчання, 2013)
The article deals with the problem of designing a model of information and communication support research activities to provide effective disclosure, dissemination and use of researching product by institutions. It is specified the concept of «information and communication support research activities» and proposed structure of information and communication support. There is proposed the model of information and communication support research activities on the EPrints basis. There is identified components such as value-targeted, informative, organizational, technological, resultative within the model. It was discovered that using the proposed model of information and communication support research activities organizes the work of researchers in the growing volume of scientific production and supports researchers’ motivation to increase its quality.